Nutritional evaluation of mature seeds of Enterolobium cyclocarpum (parota) from diverse ecological zones in western Mexico - Barrientos-Ramírez, Lucía; Vargas-Radillo, J Jesús; Segura-Nieto, Magdalena; Manríquez-González, Ricardo; López-Dellamary Toral, Fernando A (Bosque (Valdivia), 2017)
There is little information on the agroecological characteristics and chemical composition of some wild forage species in Mexico, which can be proposed as alternatives for forage uses; therefore, the aim of this work was to assess the nutritional properties of Enterolobium cyclocarpum (common name: parota) mature seeds collected from several native habitat locations with distinct physiographic and ecological conditions in Jalisco in western Mexico. Physiographic data, coexisting vegetation, environmental conditions, soil type, mineral and organic content of soils from each site were determined. Seed nutritional values (amino acid profile, mineral content and in vivo protein degradability) were evaluated by proximate composition. Seed samples from Autlán exhibited the highest crude protein values, ethyl ether extract, histidine, phosphorus, dry matter digestibility and protein efficiency ratio. This site coincides with the highest contents in soil organic carbon, soil organic matter and phosphorus, and appropriate climatic conditions; while seeds with the lowest value of crude protein, dry matter digestibility, and protein efficiency ratio were collected from Puerto Vallarla, La Huerta and Amatitán, which are the locations with inferior soil fertility characteristics.